2005
DOI: 10.1111/j.1442-9071.2005.01015.x
|View full text |Cite
|
Sign up to set email alerts
|

Epiretinal membrane surgery with or without internal limiting membrane peeling

Abstract: Internal limiting membrane removal during macular ERM surgery may minimize the recurrence of ERM, without adverse visual outcome. Further controlled prospective studies are needed to determine the role of ILM peeling in ERM surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
115
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(126 citation statements)
references
References 31 publications
5
115
0
6
Order By: Relevance
“…[8][9][10] Although evidence suggests that ERM formation may be inhibited after ILM removal, the results obtained from cases with idiopathic ERM or diabetic macular oedema may not be readily applied to diabetic eyes with active FVP because of certain unique features in the latter condition. First, a complex vitreoretinal relationship exists in diabetic FVP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] Although evidence suggests that ERM formation may be inhibited after ILM removal, the results obtained from cases with idiopathic ERM or diabetic macular oedema may not be readily applied to diabetic eyes with active FVP because of certain unique features in the latter condition. First, a complex vitreoretinal relationship exists in diabetic FVP.…”
Section: Discussionmentioning
confidence: 99%
“…4 This basement membrane scaffolding may play a role in the development of persistent macular oedema and in the proliferation, or reproliferation of ERM. 5 Earlier studies have suggested ILM peeling as an adjunct to macular surgery may improve surgical outcomes in certain macular diseases, such as macular holes, [6][7][8] epiretinal membranes, 9,10 and diabetic macular oedema; [11][12][13] however, the effect of ILM peeling in the prevention of postoperative ERM remains unknown in diabetic active FVP, which is characterized by a strong proproliferative biological environment. 14,15 To answer this question, we conducted a prospective, comparative case series study to evaluate the visual and functional outcomes of vitrectomy, with or without ILM removal, in eyes with progressive FVP.…”
Section: Introductionmentioning
confidence: 99%
“…16,37,[41][42][43] The presence of ERM overlying the ILM requires a sequential approach. To this end, the use of multiple vital stains during the same operation has been proposed, 44,45 where the first dye intends to stain ERM, while a second dye is injected after the removal of ERM to stain the ILM. Alternatively, we have demonstrated that sequential peeling may be attained with the use of a single ILM-specific vital dye.…”
Section: Discussionmentioning
confidence: 99%
“…Researches have also demonstrated that the surgical outcome is better and ERM recurrence is significantly lower in elderly ERM patients undergoing ILM peeling compared with those without ILM peeling. [17][18][19] The effect of intentional ILM peeling during ERM surgery in young patients has not been reported. In our cases, the improvement of postoperative BCVA is better than those in the earlier reports.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16] The incidence of ERM recurrences were significantly lower in elderly ERM patients undergoing ILM peeling compared with those without ILM peeling. [17][18][19] The purpose of this study was to determine the clinical features and surgical outcomes following the removal of an idiopathic macular ERM in young patients who underwent vitrectomy with ILM peeling for ERM removal.…”
Section: Introductionmentioning
confidence: 99%